Assessing the Role of International Offices in Indian and European Universities: Drivers or Facilitators - Pranjali Kirloskar; Neeta Inamdar (Ali Khorsandi Taskoh, 2021)
The international higher education space is characterized by the need felt by higher education institutions to invest in international cooperation. To compete globally, the universities strive to formulate pro-active, long-term, and sustainable internationalization strategies. Considering the direction that strategic planning at the institutional level may offer, the university management and staff in turn may look for resources and personnel to execute the internationalization vision. The role of the international office, in this regard, is instrumental in facilitating the implementation of international activities at the university. The extent to which international offices are involved in the decision-making of internationalization may be shaped by the organizational culture and management at the university. This paper largely explores if international offices play a role of a mediator or driver for international collaborations at the university. An in-depth study was conducted in two universities in India and Europe, to understand the nuances of the functioning of international offices in two diverse contexts. The method of participant observation was employed and researchers further analyzed the field notes. The findings of the study revealed that though both the international offices were involved in similar tasks, they differed concerning the organizational structures and about decision-making on internationalization.